(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
In this paper, we derive and analyze a semi-discrete Lasota-Waźewska model. First, the existence, uniqueness, and local dynamical properties of the positive fixed point are systematically investigated. Subsequently, we explore the existence of Neimark-Sacker bifurcation and the stability of the bifurcated invariant curve. Finally, numerical simulations are provided to illustrate the theoretical findings.